Bipartite molecular approach for species delimitation and resolving cryptic speciation of Exobasidium vexans within the Exobasidium genus. (June 2021) - Chaliha, Chayanika; Kaladhar, V. Chandra; Doley, Robin; Verma, Praveen Kumar; Kumar, Aditya; Kalita, Eeshan
Graphical abstract: Highlights: Species delimitation in Exobasidium ambivalent due to strong cryptic speciation. DNA barcodes for speciation limited due to scarce genetic data on Exobasidium . ITS barcode markers (∼1150 bp) developed for precise identification of E. vexans . MP, ML & BI based phylogenetic analysis confirms identity of E. vexans isolates. Molecular clock dating shows clear delineation of E. vexans isolates. Abstract: Exobasidium vexans, a basidiomycete pathogen, is the causal organism of blister blight disease in tea. The molecular identification of the pathogen remains a challenge due to the limited availability of genomic data in sequence repositories and cryptic speciation within its genus Exobasidium . In this study, the nuclear internal transcribed spacer rDNA region (ITS) based DNA barcode was developed for E. vexans, to address the problem of molecular identification within the background of cryptic speciation. The isolation of E. vexans strain was confirmed through morphological studies followed by molecular identification utilizing the developed ITS barcode. Phylogenetic analysis based on Maximum Parsimony (MP), Maximum Likelihood (ML) and Bayesian Inference (BI) confirmed the molecular identification of the pathogen as E. vexans strain. Further, BI analysis using BEAST mediated the estimation of the divergence time and evolutionary relationship of E. vexans within genus Exobasidium . The speciation process followed the Yule diversification model wherein the genus Exobasidium is approximated to have diverged in the Paleozoic era. The study thus sheds light on the molecular barcode-based species delimitation and evolutionary relationship of E. vexans within its genus Exobasidium .